The efficiency removal of oil in water (OIW) by application of milliscale air bubbles - Yusof, H A M; Razi, M A M; Yusof, M F M; Zulkifli, N F M; Setiawan, M I (2023)
The existing technology for separating oil in water (OIW) can bring harm to the environment, particularly to marine life. A new environmentally friendly technique has been proposed, involving the use of milliscale air bubbles. This study was conducted to determine the suitable retention time for injecting the milliscale air bubbles into the OIW. The significance of this study lies in its ability to separate OIW through a procedure that is environmentally safe and does not impact the ecosystem or marine life. The method used in the study involved mixing palm oil with water on a volumetric hydraulic bench. Retention times of 5 minutes, 15 minutes, 30 minutes, and 60 minutes were used in the study. The results indicated that separating oil in water required a substantial amount of time when utilizing milliscale air bubbles. In this study, a 60-minute retention time exhibited a significant number of separations, producing 512 bubbles compared to 44 bubbles generated in 5 minutes for 200 mL of oil. The longer the retention time, the more bubbles were produced. Overall, milliscale bubbles can effectively be used for the separation of oil in water